The impact of psychological empowerment of the teacher performance: A case study of the smart school system - Turi, Jamshid Ali (Universiti Malaysia Pahang, 2019)
The study has focused on the teachers’ psychological empowerment on teachers’ performance and their job satisfaction in the Smart School and College System Parachinar Campus. Quantitative and survey approach was used to assess the data collected from 50 faculty members and administrators who participated in the survey. SPSS was used to analyze the data. Independent t-test, ANOVA, regression and Pearson’s correlation was used to test hypothesis. In the end, a thorough analysis of the results was provided and a discussion was conducted followed by the conclusion of the study. Findings indicate that psychological empowerment of the faculty play significant role in the teacher performance and job satisfaction.